IgM myeloma: A multicenter retrospective study of 134 patients. Issue 8 (26th May 2017) - Castillo, Jorge J.; Jurczyszyn, Artur; Brozova, Lucie; Crusoe, Edvan; Czepiel, Jacek; Davila, Julio; Dispenzieri, Angela; Eveillard, Marion; Fiala, Mark A.; Ghobrial, Irene M.; Gozzetti, Alessandro; Gustine, Joshua N.; et al.
Abstract: IgM myeloma is a rare hematologic malignancy for which the clinicopathological features and patient outcomes have not been extensively studied. We carried out a multicenter retrospective study in patients with diagnosis of IgM myeloma defined by >10% marrow involvement by monoclonal plasma cells, presence of an IgM monoclonal paraproteinemia of any size, and anemia, renal dysfunction, hypercalcemia, lytic lesions and/or t(11;14) identified by FISH. A total of 134 patients from 20 centers were included in this analysis. The median age at diagnosis was 65.5 years with a male predominance (68%). Anemia, renal dysfunction, elevated calcium and skeletal lytic lesions were found in 37, 43, 19, and 70%, respectively. The median serum IgM level was 2, 895 mg dL −1 with 19% of patients presenting with levels >6, 000 mg dL −1 . International Staging System (ISS) stages 1, 2, and 3 were seen in 40 (33%), 54 (44%), and 29 (24%) of patients, respectively. The malignant cells expressed CD20 (58%) and cyclin D1 (67%), and t (11;14) was the most common cytogenetic finding (39%). The median overall survival (OS) was 61 months. Higher ISS score was associated with worse survival ( P = 0.02). Patients with IgM myeloma present with similar characteristics and outcomes as patients with more common myeloma subtypes.